An Analysis of the Factors that Influence the Implementation of the Policy for Monitoring Schoolchildren Meals Monitoring at Batam City - Rafqi, Ahmad; Adisasmito, Wiku Bakti Bawono (Journal of Indonesian Health Policy and Administration, 2017)
Schoolchildren are assets for the development of the nation. Therefore, healthy meals at schools are very important, because for them, it covers about 25-36% of the daily energy requirements. Unhealthy eating habits or consumption of nutrition deficient meals may cause stunting, cardiovascular diseases, cancer, diabetes, and osteoporosis. In the short term it may also cause dental caries, anemia, overweight children and obesity. Around 40-44% of meals at schools do not satisfy the food safety requirements. To increase the quality of the meals at the schools, the community should be empowered to perform independent monitoring of school meals. This is inscribed in the national action policy for safe, good-quality, and nutritious meals for schoolchildren. The aim of this research was to assess the effectiveness of the implementation of the national action policy for the snacks of schoolchildren and the factors that influences it. This was a qualitative research. The data was gathered from in-depth interviews and documentary studies and then analyzed using the policy implementation analysis of Mazmanian and Sabatier. From this research we discovered that the policy did not perform effectively in Batam City. There were no Procedure Standard Norms NSPK on the roles, tasks, and responsibilities of the implementers, there was no implementation structure, and no support from the Government and the Parliament of Batam City for the monitoring.